Non invasive trans-cutaneous bilirubin as a screening test to identify the need for serum bilirubin assessment in healthy term neonates - Gupta, BK; Chaudhary, N; Bhatia, BD; Gupta, Binod (Journal of Universal College of Medical Sciences, 2014)
INTRODUCTION: Hyperbilirubinemia is a common problem in the neonates. It can progress to develop kernicterus unless intervention is initiated. Severity of jaundice and decision for management are usually based on total serum bilirubin (TsB) estimation which technique and results closely correlates with total serum bilirubin levels. OBJECTIVES: To compare the accuracy of visual assessment of jaundice by single trained observer based on Kramer's index with total serum bilirubin levels in healthy term neonates. To compare accuracy of non invasive bilirubin assessment with serum bilirubin levels, to compare trans-cutaneous bilirubin assessment on different sites (forehead and sternum) and to develop a cutoff point oftrans-cutaneous bilirubin level for serum bilirubin assessment. METHODS: This prospective study was conducted in the Neonatal unit of the department of Paediatrics at Kasturba Hospital ,Manipal. Study period was from October 2007 to June 2008. Clinical assessment of jaundice was done in healthy term neonates by observer (Trained Paediatric Post Graduate Resident) based on Kramer's index. Transcutaneous bilirubin assessment was done on the forhead and sternum of each baby using JM-103 Minolta. Air shields bilirubino meter. Serum bilirubin level was measured within 30 minutes of the clinical assessment for each baby. RESULTS: This study included 187 healthy term neonates. The mean birth weight was 2856.83gm ± 493.89gm and mean gestation was 38.25+ 1.030 SD. Clinical assessment and Transcutaneous bilirubin(TcB) significantly correlated with total serum bilirubin (TsB), with correlation co-efficient of 0.757 and 0.801 respectively (p 0.0001). Transcutaneous bilirubin assessment over forehead showed a tendency to under estimate total serum bilirubin, with mean difference of-0.31 mg/dl, SD 1.75 mg/dl with 95% confidence interval ofthe mean -0.60 and -0.02 mg/dl (p value 0.05).Transcutaneous bilirubin assessments between 10 mg/dl to 15 mg/dl correlated accurately with total serum bilirubin levels avoiding blood sampling. CONCLUSION: Trained observer clinical assessment of jaundice can be used for screening neonatal jaundice. Non invasive transcutaneous bilirubin assessment has demonstrated significant accuracy with serum bilirubin level estimates between 48 hours to 7 days on two different sites forehead and sternum. DOI: http://dx.doi.org/10.3126/jucms.v1i4.9567 Journal of Universal College of Medical Sciences (2013) Vol.1 No.04: 17-21